2022
DOI: 10.1590/1806-9282.20220662
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and primary sarcopenia in geriatric patients

Abstract: OBJECTIVE: This study aimed to investigate the frequency of fatigue in geriatric patients with primary sarcopenia and to evaluate the relationship between fatigue and symptoms such as depression and sleepiness. METHODS: This case-control study was conducted between December 2020 and August 2021 in the geriatrics outpatient clinic of Istanbul University-Cerrahpasa. The European Working Group on Sarcopenia in Older People 2 criteria were considered for the diagnosis of sarcopenia. Demographic data, accompanying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…(Z. Chen et al, 2022;Cheng et al, 2021;Darroch et al, 2022;de Souza et al, 2021;Delibaş et al, 2021;Gao et al, 2021;He et al, 2022;Jin et al, 2021;Kirk et al, 2021;Kitamura et al, 2020;Kurita et al, 2021;Lee & Lee, 2023;Lin et al, 2022;Lu et al, 2023;Nunes et al, 2021;Suzan et al, 2022;Tan et al, 2022;Zhang et al, 2022). En la tabla 1 se muestran las características y principales resultados de los estudios que incluyeron un análisis transversal.…”
Section: Resultsunclassified
“…(Z. Chen et al, 2022;Cheng et al, 2021;Darroch et al, 2022;de Souza et al, 2021;Delibaş et al, 2021;Gao et al, 2021;He et al, 2022;Jin et al, 2021;Kirk et al, 2021;Kitamura et al, 2020;Kurita et al, 2021;Lee & Lee, 2023;Lin et al, 2022;Lu et al, 2023;Nunes et al, 2021;Suzan et al, 2022;Tan et al, 2022;Zhang et al, 2022). En la tabla 1 se muestran las características y principales resultados de los estudios que incluyeron un análisis transversal.…”
Section: Resultsunclassified
“…Sarcopenia is one of the geriatric syndromes. If left untreated over the years sarcopenia causes deterioration in basic activities of daily living, falls, cognitive impairment, and increased hospital admissions (17).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the reduction in skeletal muscle mass increases insulin resistance, which is related to the development of metabolic diseases [ 15 , 16 ], while an increase in body mass could lead to an improved insulin sensitivity [ 17 ]. It has also been observed that sarcopenia causes atherosclerosis and leads to high blood pressure [ 18 ].…”
Section: Introductionmentioning
confidence: 99%